SECONDARY AND VOCATIONAL EDUCATION IN BRAZIL (1909 -1953) (2013)
This text contextualizes the events that preceded the founding of the Brazilian federal technical schools. It exposes history paths from the Brazilian professionalizing secondary teaching. From the historical perspective that explores the schooling which has the work as an educational principle. It finds foundations on the advent of modernity, while time and historical movement for the civilizatory advancement and development. Objective to consider the secondary schooling and investigate preconized educational practices as an expression of historicity and of the continuity processes in its evolutionary process. It rises as a questioning what are the directions followed by professionalizing training in Brazil. The research avails of documental written sources. By mapping the professional education trajectory, in the described period, what is sought is to contribute to the memory register of educational institutions. It is observed that the rise of federal professionalizing schools occurred under the dominance of the agrarian-exporter capital. Its consolidation took place in processes associated to monopolization of elementary knowledge by the State and as continuity of the civilization process. The directions of the Brazilian professionalizing education took root in the tradition being fed by the industrial culture and by an ideology of progress by the work.